Sustentación de caso: propuesta de mejoras para el modelo de negocio ¨Vista Inmobiliaria¨, empresa del rubro inmobiliario - Rosales Infantas, Vanessa Milagros (2022)
In the last 3 years, the world really changed, and all businesses had 2 paths: reinvent themselves or disappear. Vista Inmobiliaria, the company chosen for this study, is a Peruvian company dedicated to offering complete advice on the process of renting and selling properties. This company chose to reinvent itself together with its main assets: its founder and an innovative service through the use of technology, such as the 360º tours. Additionally, its founder was also able to establish alliances and agreements that allowed him to make a name for himself in this competitive field. However, there are still many opportunities for improvement. It is expected that the proposals and analyzes presented in this work can contribute to future decision making and continue with the growth that has been taking place.